The Roles of Data Management and Pentahelix in Accelerating Development of Village Communities - Ni Luh Putu Agustini Karta; Ni Made Ary Widiastini; Ni Ketut Dewi Irwanti; I Nyoman Gde Prananta Bendesa (International Journal of Community Service Learning, 2023)
In various cases in villages, data is not collected properly, is not up-to-date and is not accurate. This study project’s aims to analyze the role of village management and validity of village data in accelerating development in rural communities. A qualitative descriptive method with fifty respondents from 17 villages that were successfully sampled in Bali and 9 key informants interviewed provided information related to the management of information and data systems in Cepaka Village Kediri Tabanan. The findings of this project are 1) Updating village community data is the top priority for each village so that the program launched by the government reaches the target community in need. 2) Continous public sducation about the validity of data is very important in disbursing government assistance that is right on target. 3) Competence of human resources in handling village information systems needs to be improved. 4) The availability of facilities and infrasctucture to support the village information system is absolute. 5) The collaboration of several stakeholder in the PENTAHELIX concept helps accelerate updating of village data. The conclusion of this project is that data management and PENTAHELIX contributions play an important role in accerelating developments of the village.